Regeneración por semillas en bosques nativos de Nothofagus antarctica bajo uso silvopastoril en Patagonia Sur, Argentina - Bahamonde, Héctor A.; Peri, Pablo Luis; Monelos, Lucas H.; Martínez Pastur, Guillermo José (Bosque (Valdivia))
The aim of the present study was to evaluate the effect of silvopastoral use in two pure stands of Nothofagus antarctica (ñire, ñirre) growing at two site qualities on the regeneration cycle from production and quality of seeds, and the establishment and mortality of seedling in Southern Patagonia (Argentina). To evaluate seed production four traps were distributed to capture the spatial variation of each stand during seven years (2004-2010). Also, seed viability and germination were evaluated. In each site, permanent sampling plots were used to measure seedling establishment and mortality. Seed production in stands under silvopastoral use varied from 1 to 40 million seeds ha-1, with no differences compared to seed production in surrounding primary forests of the same site quality. Stands under silvopastoral use showed that seed quality varied among sites being higher in the lower site quality. However, there was no difference in seed quality between silvopastoral use and primary forests stands. Seedling establishment was improved in the stands under silvopastoral use compared to primary forests, but mortality rate was high (or total) in all situations. We concluded that silvopastoral use of the studied stands did not modify substantially seed regeneration compared to primary forests. Los objetivos de este estudio fueron: i) evaluar la regeneración, desde el punto de vista de su producción y calidad de semillas, así como también de la instalación y supervivencia de plántulas, de dos rodales puros de Nothofagus antarctica (ñire, ñirre) bajo uso silvopastoril en distintas calidades de sitio en Patagonia Sur (51º S, Argentina); ii) comparar estos aspectos de la regeneración de ñire entre rodales bajo uso silvopastoril y bosque primario en similares condiciones geográficas y temporales. Para evaluar la producción de semillas, se usaron cuatro trampas de captura distribuidas espacialmente en cada sitio durante siete años (2004- 2010), determinándose además tamaño, viabilidad y germinación. En cada sitio, se ...